Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.ppat.1003015
|View full text |Cite
|
Sign up to set email alerts
|

InlA Promotes Dissemination of Listeria monocytogenes to the Mesenteric Lymph Nodes during Food Borne Infection of Mice

Abstract: Intestinal Listeria monocytogenes infection is not efficient in mice and this has been attributed to a low affinity interaction between the bacterial surface protein InlA and E-cadherin on murine intestinal epithelial cells. Previous studies using either transgenic mice expressing human E-cadherin or mouse-adapted L. monocytogenes expressing a modified InlA protein (InlAm) with high affinity for murine E-cadherin showed increased efficiency of intragastric infection. However, the large inocula used in these st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
135
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(141 citation statements)
references
References 67 publications
5
135
0
Order By: Relevance
“…The mouse-adapted strain of L. monocytogenes is ideal for studying oral transmission of listeriosis in mice because it can be used at doses that are 10-to 100-fold lower than the 10 9 CFU typically required to establish intestinal infection with wild-type L. monocytogenes EGDe (3,15). However, Tsai et al recently showed that the InlA m protein expressed by the mouse-adapted strain altered the tropism for L. monocytogenes in the intestinal epithelium by promoting binding to N-cadherin as well as E-cadherin (16).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mouse-adapted strain of L. monocytogenes is ideal for studying oral transmission of listeriosis in mice because it can be used at doses that are 10-to 100-fold lower than the 10 9 CFU typically required to establish intestinal infection with wild-type L. monocytogenes EGDe (3,15). However, Tsai et al recently showed that the InlA m protein expressed by the mouse-adapted strain altered the tropism for L. monocytogenes in the intestinal epithelium by promoting binding to N-cadherin as well as E-cadherin (16).…”
Section: Resultsmentioning
confidence: 99%
“…However, as a facultative intracellular pathogen, L. monocytogenes can readily survive and multiply in extracellular spaces, and there may be multiple environments that harbor extracellular bacteria during infection. For example, we previously showed that extracellular L. monocytogenes was present in the lamina propria of both the ileum and the colon after foodborne infection (3). The liver, spleen, and placenta were each shown to contain gentamicin-sensitive L. monocytogenes during systemic infection of mice or guinea pigs (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For intravenous infections, 200 l of bacterial suspension in PBS (Gibco) was administered by injection into the tail vein. Oral infections were carried out as previously described (26). Briefly, bacteria were suspended in melted butter and applied to 0.5-cm cubes of white bread.…”
Section: Methodsmentioning
confidence: 99%
“…At early time points following oral infection, recombinant L. monocytogenes invades intestinal mucosa and is later detected in the MLNs before it spreads systemically (15). Thus, we primarily focused our study on investigating γδ T cells that reside in the gutdraining MLNs.…”
Section: Monocytogenes-elicited Vγ4 + γδ T Cells Form a Tmr Populamentioning
confidence: 99%